Penerapan Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) dalam Penentuan Bantuan Siswa Miskin (BSM) pada SMK - Mesran, Mesran; Nastiti, Sindy; Sussolaikah, Kelik; Saputra, Imam; Utomo, Dito Putro (Journal of Decision Support System Research, 2024)
The BSM Program is a National Program that aims to eliminate barriers for poor students to participate by helping poor students obtain decent educational service requests, preventing dropouts, attracting poor students to return to school, helping students meet their needs in learning activities, supporting the 9-year compulsory education program (even up to high school level), and helping the smooth running of school programs. To obtain the Poor Student Assistance (BSM) funds, the government has set several criteria for who are the students who can be determined and are entitled to receive the Poor Student Assistance (BSM). These criteria will later help schools or educational institutions determine which students can be determined to receive the Poor Student Assistance Fund. Therefore, an educational institution must have a Decision Support System for recommending Poor Student Funds (BSM) using the Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) method, with the existence of a decision support system for determining Poor Student Assistance (BSM) it is hoped that the determination process will run well, be on target, and be received by those who are entitled. The final result determines that Alternative A1 is ranked first with the highest score of 22.2679. Thus, decision makers can compare the performance between the old system and the BSM fund determination decision support system using the Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) method without having to re-request data on students who will be given Poor Student Assistance funds.